Adaptation to climate change and conservation of biodiversity using green infrastructure. (27th December 2019) - Nakamura, Futoshi; Ishiyama, Nobuo; Yamanaka, Satoshi; Higa, Motoki; Akasaka, Takumi; Kobayashi, Yoshiko; Ono, Satoru; Fuke, Nao; Kitazawa, Munehiro; Morimoto, Junko; Shoji, Yasushi
ABSTRACT: In recent years, we have experienced mega‐flood disasters in Japan due to climate change. In the last century, we have been building disaster prevention infrastructure (artificial levees and dams, referred to as "grey infrastructure") to protect human lives and assets from floods, but these hard protective measures will not function against mega‐floods. Moreover, in a drastically depopulating society such as that in Japan, farmland abandonment prevails, and it will be more difficult to maintain grey infrastructure with a limited tax income. In this study, we propose the introduction of green infrastructure (GI) as an adaptation strategy for climate change. If we can use abandoned farmlands as GI, they may function to reduce disaster risks and provide habitats for various organisms that are adapted to wetland environments. First, we present a conceptual framework for disaster prevention using a hybrid of GI and conventional grey infrastructure. In this combination, the fundamental GI, composed of forests and wetlands in the catchment (GI‐1) and additional multilevel GIs such as flood control basins that function when floodwater exceeds the planning level (GI‐2) are introduced. We evaluated the flood attenuation function (GI‐1) of the Kushiro Wetland using a hydrological model and developed a methodology for selecting suitable locations of GI‐2, considering flood risk, biodiversity and the distribution of abandoned farmlands, which represent social and economic costs. The results indicated that the Kushiro Wetland acts as a large natural reservoir that attenuates the hydrological peak discharge during floods and suitable locations for introducing GI‐2 are concentrated in floodplain areas developing in the downstream reaches of large rivers. Finally, we discussed the network structure of GI‐1 as a hub and GI‐2 as a dispersal site for conservation of the Red‐crowned Crane, one of the symbolic species of Japan.